Kapital: ya sovetskuyu rossiyu v kulak sozhmu! A... pridetsya tol'ko s bezsil'noy yarost'yu kulaki szhimat'! - Lebedev, A. V (Политотдел Запасной Армии Республики и Пуокр Приволжского)
Two panel cartoon. Left panel shows capitalist attempting to stamp on Red Army soldier with flag of Soviet Russia. Right panel is capitalist pounding his arms in frustration as numerous red Soviet flags are raised Original title: Капитал: я советскую россию в кулак сожму! А... придется только с безсильной яростью кулаки сжимать! PO-1084